HERCULE POIROT AND SUPPORTS SETTLEMENT - Vlaho Akmadžić; Matej Lozančić; Matea Primorac (e-Zbornik. Elektronički Zbornik Radova Građevinskog Fakulteta)
The inspiration for writing this paper lies in the character of Hercule Poirot, a fictional Belgian detective who appears in the Agatha Christie novel series. In the television series, the detective role was played by actor David Suchet. The paper, which builds on a series of works related to the phenomenon of support settlement, the occurrence of cracks and the determination of the soil reaction coefficient, shows the connection between the shape of the mustache of the actor mentioned in the series and the settlement of the middle support of a continuous girder over two spans. The sought answer was found by observing the area between the limit cases of the bending moment diagram following fractal logic.